Healing Minds, Changing Lives : A Movement for Community-Based Mental Health Care in Peru – Delivery Innovations in a Low-Income Community, 2013-2016 - World Bank Group (World Bank, Washington, DC, 2018)
This report explores community-focused change initiatives in the financing, organization, and delivery of mental health services in Peru from 2013 to 2016. It examines the national dimension of reforms but focuses above all on implementation and results in the economically fragile district of Carabayllo, in northern Lima.